Understanding your users : a practical guide to user research methods - Baxter, K. ; Courage, C. & Caine, K. (Amsterdam Elsevier, 2015)
This new and completely updated edition is an easy to implement, hands-on resource for usability in the real world. You'll learn about the user requirements gathering stage of product development and find a variety of techniques. For each technique, you'll understand how to prepare for and conduct the activity, as well as analyze and present the data - all in a practical and hands-on way. Each method presented provides different information about the user and their requirements (e.g., functional requirements, information architecture, task flows). The techniques can be used together to form a complete picture of the users' requirements or they can be used separately to address specific product questions. These techniques have helped product teams understand the value of user requirements gathering by providing insight into how users work and what they need to be successful at their tasks. You'll find case studies from industry-leading companies to demonstrate each method in action. After reading this book, you'll be able to conduct any usability activity (e.g., getting buy-in from management, legal and ethical considerations, setting up your facilities, recruiting, and moderating activities) and be able to apply them to your own products.
Catherine Courage was the first author of the previous edition.
Keywords: Human-computer interaction; Computer software - Development; User interfaces (Computer systems); Computer software - Development; Human-computer interaction; User interfaces (Computer systems)